Clinical and ultrasound correlations in patients with ischemic stroke and viral infection manifestation in anamnesis - Turchyna Наталія; Cherenko Тетяна; Heletiuk Юлія; Trepet Лариса (Psychosomatic Medicine and General Practice, 2020)
The goal. The goal of the work was to study the structure of viral and non-viral infections in patients with ischemic stroke, as well as the relationship between neurological recovery and severity of cerebral atherosclerosis, depending on the type of infectious agent. Materials and methods. A total of 89 patients with ischemic acute cerebral circulation disorder and a history of clinical manifestations of a viral infection in the 3 months prior to the cerebrovascular accident were included in the study. Among the patients 44 (44.9%) were men and 54 (55.1%) were women with an average age of 62.08 ± 1.29 years (from 36 years to 92 years). 61 (81.9%) patients were diagnosed with ischemic stroke, and 28 (18.1%) patients were diagnosed with TIA. The diagnosis was confirmed by magnetic resonance imaging (MRI), and the severity of neurological status was assessed using the National Institute of Health Stroke Scale (NIHSS) on the first, 7th and 21st day. Patients’ blood serum was examined for the presence of herpes viruses DNA, the RNA of influenza viruses, enteroviruses, the viruses of an acute respiratory infection (adenoviruses), as well as for the common non-viral infections: mycoplasma, ureoplasma, toxoplasma, and chlamydia. The method of polycytomerase chain reaction (PCR) for DNA and RNA viruses extraction from blood serum (6; 8) and the method of enterovirus antigens detection in a cell culture by enzyme-linked immunosorbent assay (ELISA) (21; 24; 40) were used. The degree of cerebral atherosclerosis was determined by ultrasound duplex scanning (UDS) of brachiocephalic arteries. Methods of descriptive statistics were used. Research results. The average period from the clinical manifestation of the infection to the development of stroke in patients with viral persistence was 11.8 ± 2.5 days (from 1 day to 90 days). Up to 7 days — 32 (36.0%) patients, from 7 days to 14 days inclusive — 44 (49.4%), more than 14 days — 13 (14.6%). There was a weak but definite inverse correlation between the term of the viral manifestation and the severity of the acute cerebrovascular accident (r = 0.237, p = 0.025). HSV1 (51) was detected most often in the acute period of stroke in 57% of patients, (p <0.05). The persistence of HSV2 and HHV6 was 38.2% and 32.6% respectively. A combination of two different HSV2 and HHV6 viruses was observed in 84 (89.9%) patients. The combination of HSV1 / HSV2 is most commonly observed (in 29 (32.6%) patients p <0.05). Coefficients of correlation between the presence of certain types of viruses, the number of stenoses, and the number of hemodynamically significant stenoses ranged from 0.19 with ARI to 0.33 in the case of a combination with HHV6. There was no detectable relationship between the severity of neurological deficiency on the first day after the stroke and the type of viral infection or a combination thereof, except for adV (r = 0.27, p = 0.01). The reduction in the NIHSS score on the 7th and the 21st day negatively correlated with the presence of certain viruses and their combinations, in particular herpesviruses or their associations HSV1, HSV1,2; HSV1,2-HHV6. Conclusion. The DNA of HSV1, HSV2, HHV6, HHV4, HHV5 viruses was most often found in patients with ischemic stroke and a clinical manifestation of a persistent viral infection in history (within 1-90 days before the development of symptoms), The presence of major vessels stenosis in the extracranial unit, the number of stenoses, and the presence of hemodynamically significant stenoses correlated with the presence of viral persistence of HHV6 and / or the association of HHV6 and influenza. The presence of HSV1, HSV2, HHV6 viruses and / or their associations worsens the restoration of neurological functions in the acute post-ischemic period setting.